2019
DOI: 10.2147/ahmt.s196080
|View full text |Cite
|
Sign up to set email alerts
|

<p>Older siblings' influence on sexual behavior of high school adolescents in Mekelle, northern Ethiopia</p>

Abstract: Background: Older siblings are one of the key sources of beliefs about sexual activity, including safe sexual practices, and can even exert pressure to engage in sexual activities. This effect persists beyond parental supervision and peer pressure. Despite this, although a considerable body of research has examined parental and peer influence, comparable data on older sibling influence on younger adolescent sexual behaviors are scant, and this area needs in-depth analysis. Objective: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…-At least one older sibling alive (no-ref. ; yes): although studies agree on older siblings' influence, disagreements prevail on whether the older sibling's role is positive or negative (Rodgers, Rowe, & Harris, 1992;Haftu, Berhe, Tesfay, & Gebremeskel, 2019). The majority emphasise how older siblings' behaviours can negatively influence their younger siblings' sexual conduct (Whiteman, Zeiders, Killoren, Rodriguez, & Updegraff, 2014;Widmer, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…-At least one older sibling alive (no-ref. ; yes): although studies agree on older siblings' influence, disagreements prevail on whether the older sibling's role is positive or negative (Rodgers, Rowe, & Harris, 1992;Haftu, Berhe, Tesfay, & Gebremeskel, 2019). The majority emphasise how older siblings' behaviours can negatively influence their younger siblings' sexual conduct (Whiteman, Zeiders, Killoren, Rodriguez, & Updegraff, 2014;Widmer, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding modeling, younger siblings may look to older siblings as examples of appropriate behavior. Studies of African (Haftu et al, 2019), Canadian (Wall-Wieler et al, 2016), and Mexican-origin (Coleman-Minahan & Scandlyn, 2017 girls have found that if an older sister becomes pregnant or engages in risky sexual behaviors, the younger sister is more likely to as well. Adolescent girls may also try to learn from the mistakes they perceive their older sisters have made (Killoren & Roach, 2014).…”
Section: Siblings and Extended Familymentioning
confidence: 99%